Efecto de una bebida lactea a base de cocoa sobre la presión arterial y la función endotelial en pacientes con insuficiencia cardiaca: ensayo clínico aleatorizado, a doble ciego, controlado con placebo. Effect of a cocoa milky drink on arterial pressure and endothelial function of patients with heart failure: a randomized, double-blinded and placebo-controlled clinical trial. - Patricia Montaño Hernández; Juan J. Orozco Gutierrez; Lillia Castillo Martínez; Arturo Orea Tejeda; Nosthas Lorena Cassis; Francisco Ubeda; Gabriela Belio; Elsa C. Muñoz (ECIMED, 2011)
Introduction There is evidence that chocolate, rich in flavonoids, may have the potential toimprove cardiovascular health. The beneficial cardiovascular effects of flavonoidsare attributed to their ability to improve endothelial function, throughthe nitric oxide system and so the blood pressure decreases.Objective To determine the effect of intake liquid dark chocolate rich in flavonoids onendothelial function and blood pressure in heart failure adults.Method Randomized, placebo-controlled, clinical trial. We included 30 adults that wererandomly assigned to consume a milk drink with dark chocolate rich in flavonoids(95g/day) or placebo chocolate-flavored milk cocoa-free. Outcomes:Change in body composition was measure by bioelectrical impedance (RJL), inblood pressure with stress test and endothelial function (TAM/TT index) withphotopletysmography.Results Control group: mean age 75,8±8,35; BMI 28,5±4,68 and intervention groupmean age 64,7±12,18; BMI 35,6±10,16; symptoms (dyspnea, fatigue, edema)and weight decreased (90,9±27,4 compared with 89,6±28,6 p=0,05) inthis last group, while in the control group all of these increased. Blood pressuredecreased after the ingestion of dark chocolate (systolic 4,1 and diastolic11%) compared with placebo; in control group systolic blood pressure decrease3,8% and diastolic increase. Dark chocolate ingestion improved endothelialfunction measured as TAM/TT index (40,50±12,3 compared with32,18±6,5 p=0,05) compared with placebo (42,57±15,4 compared with36,48±10,9 p=0,12).Conclusions The chronic ingestion of dark chocolate rich in flavonoids for 4 weeks improvedendothelial function in heart failure patients.